2004
DOI: 10.1111/j.1523-1755.2004.00512.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma cytokine levels predict mortality in patients with acute renal failure

Abstract: There is evidence of ongoing SIRS with concomitant CARS in critically ill patients with ARF, with higher levels of plasma IL-6, IL-8, and IL-10 in patients with ARF who die during hospitalization. Strategies to modulate inflammation must take into account the complex cytokine biology in patients with established ARF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
288
6
12

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(324 citation statements)
references
References 31 publications
10
288
6
12
Order By: Relevance
“…However, to date, direct proinflammatory cytokine manipulation (e.g., TNF-␣ and IL-1 pathway interruption) in patients with established sepsis has not been fruitful (37)(38)(39). Increased plasma levels of IL-6 predict mortality in patients with sepsis and in patients with sepsis and acute kidney disease (40,41). We have shown that IL-6 also predicts the development of AKI and need for RRT in patients with SS.…”
Section: Discussionmentioning
confidence: 82%
“…However, to date, direct proinflammatory cytokine manipulation (e.g., TNF-␣ and IL-1 pathway interruption) in patients with established sepsis has not been fruitful (37)(38)(39). Increased plasma levels of IL-6 predict mortality in patients with sepsis and in patients with sepsis and acute kidney disease (40,41). We have shown that IL-6 also predicts the development of AKI and need for RRT in patients with SS.…”
Section: Discussionmentioning
confidence: 82%
“…We suggest that the exuberant proinflammatory response in AKI contributes to the development of respiratory failure, which may be less in ESRD. Proinflammatory cytokines such as IL-6, IL-8 and TNF-α are increased in patients with AKI, 16 and increased levels of IL-6 and IL-8 predicted prolonged mechanical ventilation in patients with AKI. 15 The inflammatory nature of AKI and the resultant effect on the lungs is highlighted by studies in animal models demonstrating that inflammatory genes are up-regulated in the kidney and lung 32 and that anti-inflammatory treatment with IL-6 inhibition, 33 α-MSH 34 or a p38 MAP kinase inhibitor 35 protect against lung injury in animal models of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…For example, increased proinflammatory cytokines associated with AKI may contribute to extra-renal organ dysfunction such as acute lung injury (ALI). [13][14][15][16] Furthermore, recent attention has been given to the role of fluid overload as a factor associated with increased mortality in patients with AKI. [17][18][19] Many of the factors associated with increased mortality in patients with AKI are likely to be absent in patients with end-stage renal disease (ESRD).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, infusion of a tumor necrosis factor (TNF)-α binding protein decreased neutrophil infiltration and preserved renal function, suggesting a deleterious role for the upregulation of TNF-α in renal I/R (136). In addition, levels of the pro-inflammatory cytokines IL-6 and IL-8 in plasma have been found to predict mortality in patients with acute renal failure (137).…”
Section: Activation Of Inflammation and Endothelial-leukocyte Interacmentioning
confidence: 99%